2010
DOI: 10.1002/jssc.200900864
|View full text |Cite
|
Sign up to set email alerts
|

Separation of flavonoid and alkaloid using collagen fiber adsorbent

Abstract: Flavonoids and alkaloids are two major classes of plant compounds with biological activities, and they usually coexist in many medicinal herbs. In this study, a novel collagen fiber adsorbent (CFA) was prepared, and its application for adsorption chromatography separation of flavonoids and alkaloids was systematically investigated. The typical flavonoids, rutin and baicalin, and the typical alkaloids, matrine and caffeine, were selected as probe molecules for the investigations. The batch adsorption behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…26 As shown in our previous work, CFA well keeps the uniform fibrous structure of collagen fiber. 26 It has been reported that the adsorbents with fibrous structure usually have a higher mass transfer rate and a lower back pressure in comparison with conventional porous materials, such as porous silica gel and macroporous resin, 33 which promise that CFA can be used in high flow rate though it has lower mechanical strength than silica gel and macroporous resin. So the fibrous structure of CFA may be beneficial to large-scale application.…”
Section: Resultsmentioning
confidence: 75%
“…26 As shown in our previous work, CFA well keeps the uniform fibrous structure of collagen fiber. 26 It has been reported that the adsorbents with fibrous structure usually have a higher mass transfer rate and a lower back pressure in comparison with conventional porous materials, such as porous silica gel and macroporous resin, 33 which promise that CFA can be used in high flow rate though it has lower mechanical strength than silica gel and macroporous resin. So the fibrous structure of CFA may be beneficial to large-scale application.…”
Section: Resultsmentioning
confidence: 75%
“…Compared with other compounds in plant extracts, the abundant phenolic hydroxyls of tannin ensured its high affinity to GCF through multipoint hydrogen bond interactions, thus exhibiting excellent adsorption selectivity. In another investigation, we also found that GCF could separate alkaloids from flavonoids because nitrogen‐containing alkaloids exhibited a lower hydrogen bonding ability compared with hydroxyl‐containing flavonoids . All these studies imply that the bioactive compounds in plant extracts may be separated by using GCF if there are differences in the hydrogen bond formation between the compounds and collagen fibre.…”
Section: Introductionmentioning
confidence: 77%
“…In another investigation, we also found that GCF could separate alkaloids from flavonoids because nitrogen-containing alkaloids exhibited a lower hydrogen bonding ability compared with hydroxyl-containing flavonoids. 23 All these studies imply that the bioactive compounds in plant extracts may be separated by using GCF if there are differences in the hydrogen bond formation between the compounds and collagen fibre. The number and the position of the hydroxyl groups in phenol compounds will significantly affect their hydrogen bonding capacities.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the common extraction method for alkaloids is LLE including base, acid, and alcohol extraction. Unfortunately, the inefficient extraction yield of alkaloids from crude plants limited their application . In addition, waste liquid from alkaline or acid solution extraction resulted in environmental and after‐treatment issues.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the common extraction method for alkaloids is LLE including base, acid, and alcohol extraction. Unfortunately, the inefficient extraction yield of alkaloids from crude plants limited their application [1][2][3][4]. In addition, waste liquid from alkaline or acid solution extraction resulted in environmental Article Related Abbreviations: AIBN, azodiisobutyronitrile; CAF, caffeine; CPT, (s)-(+)-camptothecin; EGMRA, ethylene glycol maleic rosinate acrylate; EVO, evodiamine; HAc, acetic acid; HCPT, (s)-10-hydroxycamptothecin; MAA, methacrylic acid; MeOH, methanol; MPTMS, 3-(methacryloyloxy)-propyltrimethoxysilane; RPS, rosin-based polymer-bonded silica particle; RPS-column, rosin-based polymer bonded silica HPLC column; Rs, resolution; RUT, rutecarpine; TEO, theophylline.…”
Section: Introductionmentioning
confidence: 99%